The end of a participant's research journey: the expected path and the alternatives. - Pluess-Hall, Helen (British Journal of Nursing, 2025)
This article discusses the expected and the alternative research journeys for clinical trial participants. It examines the stages when a participant may leave a trial, the reasons for alternative endings, and the impact of exiting a trial on both participants and health professionals. The participation of patients and healthy volunteers is essential for treatments and care to be advanced. Research is no longer only the concern of dedicated clinical research nurses; it forms a pillar of nursing practice and the Chief Nursing Officer for England's Strategic Plan for Research applies to nurses in all roles, with the aim of research being embedded within the NHS. Therefore, nurses need an awareness and understanding of a patient's clinical trial journeys to provide appropriate support and care.